1974
DOI: 10.1159/000468121
|View full text |Cite
|
Sign up to set email alerts
|

Amenorrhea in Endogenous Depression

Abstract: Five patients are presented in whom reproductive abnormalities and depression were both reversed with imipramine. Although much clinical and experimental work lies ahead before the relationship of hypothalamic hormones and depression is understood, current research pertaining to hypothalamic releasing factors provides many clues which fit quite well with both clinical observations and current theories regarding a neuroendocrinological pathogenesis of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Only one case of induced acne has been described with this molecule. [35] Imipramine In 1974, Ossofsky [36] reported two cases of imipramineinduced acne in a study of five patients that investigated the role of imipramine in amenorrhea and endogenous depression. To date, there have been no additional reports of imipramineinduced acne.…”
Section: Maprotilinementioning
confidence: 99%
“…Only one case of induced acne has been described with this molecule. [35] Imipramine In 1974, Ossofsky [36] reported two cases of imipramineinduced acne in a study of five patients that investigated the role of imipramine in amenorrhea and endogenous depression. To date, there have been no additional reports of imipramineinduced acne.…”
Section: Maprotilinementioning
confidence: 99%
“…Amineptine and its products were found in serum, urine, and skin lesions, and histological examinations showed that this drug may result in keratinizing syringometaplasia in neutrophilic eccrine hidradenitis and eccrine glands [18]. Tricyclic antidepressants such as maprotiline [19] and imipramine [20] are also known to cause acneiform eruptions.…”
Section: Tricyclic Antidepressantsmentioning
confidence: 99%